PEMETAAN KOSENTRASI LIMBAH MINYAK PADA AIR TANAH DI DAERAH KELURAHAN TALANG MANDI KECAMATAN MANDAU KABUPATEN BENGKALIS PROVINSI RIAU - Hilda Yetri; Helfia Edial; Triyatno triyatno (JURUSAN GEOGRAFI FIS UNP, 2017)
This research was purpose (1) to find out the spread of waste oil around petroleum mining in Talang Mandi urban village. (2) to find out pollution levels on groundwater which has been contaminated by waste oil in Talang Mandi, Mandau village. Research shows that : (1) waste generated by the mining contaminate ground water or water. (2) from 9 samples, wells 1 has the highest sulfur content that is numbered 0,009 mg/L, while, wells 8 and 9 the lowest in same number 0,001 mg/L, (3) based on 9 samples, wells 1 has the highest ammonia content that is numbered 0,472 mg/L, while wells 9 has the lowest that is numbered 0,153 mg/L. (4) the highest DO levels found in wells 9 that is numbered 7,01 mg/L, while the lowest DO levels found in wells 1 that is numbered 5,86 mg/L. The higher DO levels in the water it will make it better. (5) wells 1 has the highest nickel content with 0,083 mg/L, while wells has the lowest with 0,043 mg/L. (6) wells 1 has the highest natrium content with 258,33 mg/L, while wells 5 has the lowest with 177,28 mg/L. Then the result is mapped.